2017
DOI: 10.18535/jmscr/v5i8.31
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Trend of Caesarean Rates in India: Evidence from NFHS-4

Abstract: Background: Caesarean section (CS) rate is increasing worldwide and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Private institutions conduct more csections than public institutions. There is a greater chance of unnecessary cesarean being conducted by private institutions for their economic motives [4]. This statistical analysis is of concern and has predisposed several risks to the development and health of the child.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Private institutions conduct more csections than public institutions. There is a greater chance of unnecessary cesarean being conducted by private institutions for their economic motives [4]. This statistical analysis is of concern and has predisposed several risks to the development and health of the child.…”
Section: Introductionmentioning
confidence: 99%
“…Many strains of E. faecalis produce bacteriocins called enterocins, a family of safe [16] and ribosomally synthesized antimicrobial peptides that inhibit pathogenic organisms [17]. There are many factors known to influence the composition of the microbial flora in infants during and after birth [1,2,4]. Several researchers have observed that preterm infants and csection-delivered infants exhibited a delayed intestinal colonization along with a smaller number of species variability and a higher rate of potentially pathogenic microorganisms [6,8,9,18].…”
Section: Introductionmentioning
confidence: 99%